Molecular characterization of canine parvovirus type 2 (CPV2) reveals a high prevalence of the CPV2c genotype among dogs suffering from diarrhea - Sajid Umar; Di Gao; Semin Kim; Yixi Cheng; Zhenkun Fang; Qiu Zhongqi; Weidong Yu; Benjamin D. Anderson (BMC, 2024)
Abstract Canine parvovirus 2 (CPV-2) is a highly contagious virus in dogs that typically causes hemorrhagic enteritis and a high mortality rate in unvaccinated puppies. The genetic variability and antigenic diversity of CPV-2 hinder its effective prevention of infection by vaccination. To investigate the epidemiology and genetic characteristics of CPV-2 in China, rectal swabs from affected dogs were collected from different animal clinics in Kunshan from 2022 to 2023. Preliminary detection and capsid gene sequencing of CPV-2 were performed using previously described primers and protocols. The overall detection rate for CPV-2 was 16.5% (33/200). A significant association was found between the CPV-2-positivity and clinical signs, age, breed and vaccination status. Sequence analysis revealed the presence of CPV-2c genotypes in all positive samples, which were genetically similar to other Asian CPV-2c strains. Notably, four key mutations (A5G, F267Y, Y324I and Q370R) were detected in all isolates, and one novel mutation (I447M) was detected in three CPV-2 isolates. These mutations in the CPV-2 strains could impact vaccine efficacy and the effectiveness of the virus immune evasion. Surprisingly, no recombination events were observed between the identified CPV-2c strains and reference strains from China. Our data revealed that amino acid residues 324, 426 and 440 of VP2 may under strong selection pressure. This pattern of genetic variation in the CPV-2 lineage warrants continuous laboratory-based surveillance programs in other parts of China to better understand the pattern of seasonal distribution and association between emerging genotypes and the intensity of disease severity.